Maturity status influences perceived training load and neuromuscular performance during an academy soccer season - Salter, J.; Julian, R.; Mentzel, S. V.; Hamilton, A.; Hughes, J. D.; De St Croix, M. (Research in Sports Medicine, 2024)
Commonly we see large within-age-group variations in physique, including body mass, stature, and percentages of predicted adult height, which suggests that age-specified training loads are flawed. Aims were to investigate how maturation impacts training load and neuromuscular response within academy soccer and to provide recommendations for practitioners. Fifty-five male soccer players (age 14.5 ± 1.2 years; stature 172 ± 10 cm; body mass 59.8 ± 10 kg; 94.1 ± 1.8% predicted adult height) reported differential ratings of perceived exertion (AU) across a season. Neuromuscular performance (countermovement jump, reactive strength index, absolute and relative leg stiffness) was measured at three time points across the season. Perceived exertion and neuromuscular performance were examined using linear mixed modelling, supplemented with non-clinical magnitude-based decisions. Analysis indicates every 5% increase in maturity status results in players perceiving overall session intensity 6.9 AU lower and 13.9 AU lower for a 10% maturity shift. Both 5% and 10% changes in maturity most likely resulted in higher countermovement jump, with likely to very likely differences observed for RSI and ABS. Maturity substantially influences neuromuscular performance over the season. Therefore, maturity-specific load prescription may prevent significant within age-group differences in accumulated load, possibly reducing injury risk and/or burnout.